R-T-B rare earth permanent magnet material and preparation method and application thereof
By optimizing the concentration distribution of Rx and Rh in R-T-B rare earth permanent magnet materials, the problems of limited improvement in magnetic performance and reduced magnet consistency in the prior art are solved, and higher magnet uniformity and squareness are achieved, which significantly improves magnet properties. able.
Patent Information
- Application Number
- CN202411642531.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
When the existing R-T-B system rare earth permanent magnet materials introduce heavy rare earth elements during grain boundary diffusion, the magnetic performance improvement is limited, the overall consistency of the magnets decreases, and the squareness deteriorates.
By introducing Rx and Rh into R-T-B rare earth permanent magnet material, the concentration distribution of Rx satisfies: grain boundary phase > main phase grain epitaxial layer > main phase grain core ≥ main phase grain surface layer, and the concentration distribution of Rh satisfies: main phase The grain surface layer > grain boundary phase ≥ main phase grain epitaxial layer > main phase grain core, the formation energy of Rx is lower than Rh, inhibits the agglomeration of Rh and promotes the diffusion depth of Rh.
The magnet uniformity and squareness of R-T-B rare earth permanent magnet materials are improved, and the magnetic performance is significantly improved, especially the intrinsic coercive force and residual magnetic performance at room temperature and high temperature.
Smart Images

Figure CN119480411A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an RTB rare earth permanent magnetic material and a preparation method and application thereof. Background Art
[0002] RTB rare earth permanent magnet materials introduce heavy rare earth elements (such as Dy or Tb) through grain boundary diffusion technology to increase the coercivity Hcj of the magnet while keeping the remanence Br basically unchanged. However, during the grain boundary diffusion process, the content of heavy rare earth diffused to the center of the magnet is limited.
[0003] In order to improve the diffusion efficiency, the prior art reduces the melting point of grain boundaries by regulating the grain boundaries. For example, CN115020057A mentions that the diffusion matrix is composed of a NdFeB main phase alloy and a light rare earth alloy R Lx M 1-x The NdFeB material comprises a main phase, a Nd-rich phase and a M-rich low melting point shell layer located between the main phase and the Nd-rich phase, wherein the Nd-rich phase is composed of R L and its oxides, M being a non-rare earth element.
[0004] However, this method will simultaneously accelerate the diffusion of the surface layer, making it extremely easy for the surface heavy rare earth to enter the main phase of the grain, resulting in limited improvement in magnetic properties, decreased overall consistency of the magnet, and worsening squareness. Summary of the invention
[0005] The present invention is to solve the problem in the prior art that when heavy rare earth elements are introduced into RTB rare earth permanent magnet materials by grain boundary diffusion, the magnetic properties are limitedly improved, the overall consistency of the magnet decreases, and the squareness deteriorates. The present invention provides an RTB rare earth permanent magnet material and a preparation method and application thereof. The grain boundary diffusion depth in the RTB rare earth permanent magnet material is increased, and the uniformity of the magnet is further improved, and the squareness is improved.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an RTB rare earth permanent magnet material, which comprises a main phase grain and a grain boundary phase, wherein the main phase grain comprises, from the outside to the inside, a main phase grain surface layer, a main phase grain epitaxial layer and a main phase grain core;
[0008] The RTB rare earth permanent magnet material includes Rx and Rh, and Rx includes praseodymium (Pr), holmium (Ho), erbium (Er) (Er), Thulium (Tm), Yttrium (Y) and lutetium (Lu), Rh includes dysprosium (Dy) and / or terbium (Tb);
[0009] The concentration distribution of Rx satisfies: grain boundary phase>main phase grain epitaxial layer>main phase grain core≥main phase grain surface layer, and the concentration of Rx refers to the ratio of the mass of Rx at that location to the mass of the RTB rare earth permanent magnet material;
[0010] The concentration distribution of Rh satisfies: surface layer of main phase grain>grain boundary phase≥epitaxial layer of main phase grain>core of main phase grain, and the concentration of Rh refers to the ratio of the mass of Rh at that location to the mass of the RTB rare earth permanent magnet material.
[0011] In the present invention, the definition of the RTB rare earth permanent magnet material is conventional in the art, that is, it refers to a permanent magnet material composed of R, T and B and unavoidable impurities, and the material of the main phase grain is R2Fe 14 B, wherein R is one or more rare earth elements, T contains at least Fe, and is a non-rare earth transition metal with Fe as an essential element, and B refers to boron.
[0012] In the present invention, the RTB rare earth permanent magnet material may further include an M element, where M is one or more of Cu, Al, Co, Ga, Zr and Ti.
[0013] In the present invention, the Rx is a rare earth element having a formation energy lower than that of the Rh.
[0014] In the present invention, Rx can be introduced in the form of a multi-element alloy component, and Rh can be introduced through grain boundary diffusion. Since the formation energy of Rx at the grain boundary is lower than that of Rh, a special distribution of Rx can be formed in the material, which inhibits the agglomeration of Rh at the grain boundary and promotes the diffusion depth of Rh.
[0015] In some embodiments, Rx is introduced in the form of a multi-element alloy component and Rh is introduced by grain boundary diffusion.
[0016] In other embodiments, Rx is introduced in the form of a multi-element alloy component, a portion of Rh is introduced by grain boundary diffusion, and a portion of Rh is introduced in the form of a multi-element alloy component.
[0017] In the present invention, the ratio of the concentration of Rx in the core of the main phase grain to the concentration of Rx in the surface layer of the main phase grain may be (1.0-2.5):1, for example, 1.8:1.1, 1.9:0.8, 2.2:1.3, 1.7:0.7 or 2.1:1.2.
[0018] In the present invention, the ratio of the concentration of Rx in the surface layer of the main phase grains to the concentration of Rx in the epitaxial layer of the main phase grains may be 1:(3.0-6.0), for example, 1.1:3.8, 0.8:3.7, 1.3:4.2, 0.7:3.6 or 1.2:4.1.
[0019] In the present invention, the concentration of Rx in the main phase crystal grain epitaxial layer is equal to the concentration of Rx in the grain boundary phase. The ratio of degrees can be 1: (2.0-3.0), for example, 3.8:8.7, 3.7:8.6, 4.2:9.1, 3.6:9.5 or 4.1:8.9.
[0020] In the present invention, the ratio of the Rh concentration in the core of the main phase grain to the Rh concentration in the surface layer of the main phase grain may be 1:(15.0-20.0), for example, 0.48:7.8, 0.45:8.5, 0.51:8.6, 0.53:9.0 or 0.50:8.2.
[0021] In the present invention, the ratio of the Rh concentration in the surface layer of the main phase grains to the Rh concentration in the epitaxial layer of the main phase grains may be (2.0-2.5):1, for example, 7.8:3.6, 8.5:3.7, 8.6:3.5, 9.0:4.5 or 8.2:3.9.
[0022] In the present invention, the ratio of the Rh concentration of the main phase grain epitaxial layer to the Rh concentration of the grain boundary phase may be 1:(1.0-1.2), for example, 3.6:3.8, 3.7:3.9, 3.5:4.1, 4.5:5.2 or 3.9:4.0.
[0023] In the present invention, preferably, in the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of at least 600 μm from the surface, the Rh concentration distribution satisfies: main phase grain surface layer>grain boundary phase≥main phase grain epitaxial layer>main phase grain core.
[0024] In the present invention, preferably, in the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 800 μm from the surface, the concentration distribution of Rh can satisfy: main phase grain surface layer>grain boundary phase≥main phase grain epitaxial layer>main phase grain core.
[0025] In the present invention, preferably, within the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of at least 600 μm from the surface, the concentration distribution of Rx satisfies: grain boundary phase>main phase grain epitaxial layer>main phase grain core≥main phase grain surface layer.
[0026] In the present invention, preferably, in the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 800 μm from the surface, the concentration distribution of Rx can satisfy: grain boundary phase>main phase grain epitaxial layer>main phase grain core≥main phase grain surface layer.
[0027] In the present invention, the concentration distribution of Rh may also satisfy: |C 0-200 -C 200-400 |≤1%,|C 200-400 -C 400-600 |≤1%,C 0-200 It refers to the integrated average value of the concentration of Rh in the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 200 μm from the surface, C 200-400It refers to the integral average value of the concentration of Rh in the interval from 200 μm to 400 μm vertically away from the surface in the RTB rare earth permanent magnet material, C 400-600 It refers to the integrated average value of the Rh concentration in the interval from 400 μm to 600 μm vertically away from the surface in the RTB rare earth permanent magnet material.
[0028] In the present invention, the concentration of Rx and the concentration of Rh in the RTB rare earth permanent magnet material are both measured by a field emission electron probe microanalyzer.
[0029] In some embodiments of the present invention, the RTB rare earth permanent magnet material is a cylindrical or square magnet.
[0030] In these embodiments, the thickness of the cylindrical or square magnet is preferably 6-20 mm, such as 8 mm.
[0031] In a second aspect, the present invention further provides a method for preparing a RTB rare earth permanent magnet material, which comprises the following steps:
[0032] S1, smelting, casting, powdering, pressing and sintering the first alloy and the second alloy to obtain a substrate;
[0033] The first alloy includes R1, Fe and B elements, and the second alloy includes R2, Fe and B elements; R1 includes one or more of Nd, Dy and Tb, and R2 includes Rx, and Rx includes one or more of Pr, Ho, Er, Tm, Yttrium and Lu;
[0034] In the substrate, the content of Rx is 0.2%-1%, and the percentage is the ratio of the mass of Rx to the mass of the substrate;
[0035] S2, performing grain boundary diffusion on the substrate using a diffusion source containing Rh, wherein Rh includes Dy and / or Tb;
[0036] S3, subjecting the diffusion treated substrate to aging treatment.
[0037] In the present invention, in step S1, the total amount of all rare earth elements R can be 29%-36%, preferably 30.2%-30.4%, where the percentage is the ratio of the mass of all rare earth elements R to the mass of the substrate.
[0038] In the present invention, in step S1, the substrate may further include an M element, where M is one or more of Cu, Al, Co, Ga, Zr and Ti. The M element may come from the first alloy and / or the second alloy.
[0039] In the present invention, in step S1, the content of Rx in the substrate is 0.3%-1%, for example, 0.32%, 0.40%, 0.60%, 0.80% or 0.99%.
[0040] In the present invention, in step S1, the content of R1 in the first alloy may be 29%-36%, for example, 30.21%, where the percentage is the ratio of the mass of R1 in the first alloy to the mass of the first alloy.
[0041] In the present invention, in step S1, the content of the B element in the first alloy may be 0.8%-1.0%, for example, 0.95%, where the percentage is the ratio of the mass of the B element in the first alloy to the mass of the first alloy.
[0042] In the present invention, in step S1, the first alloy may further include an M element, where M is one or more of Cu, Al, Co, Ga, Zr and Ti.
[0043] Preferably, the first alloy further comprises one or more of Al, Cu and Ga. The total amount of Al, Cu and Ga in the first alloy may be less than 1.5%, for example, 0.4%, where the percentage is the ratio of the sum of the mass of the Al, Cu and Ga elements in the first alloy to the mass of the first alloy.
[0044] In a specific embodiment of the present invention, the composition of the first alloy is: Nd 22.28%, Dy 0.5%, Pr 7.43%, Fe 67.25%, Co 1%, Cu 0.2%, Ga 0.2%, B 0.95% and Ti 0.2%, and the percentage is the ratio of the mass of each element in the first alloy to the mass of the first alloy. The Nd and Pr elements in the first alloy can come from a PrNd alloy.
[0045] In the present invention, in step S1, the content of R2 in the second alloy may be 29%-36%, such as 31%, 32%, 33%, 35% or 36%, where the percentage is the ratio of the mass of R2 in the second alloy to the mass of the second alloy.
[0046] In the present invention, in step S1, the content of Rx in the second alloy may be 10%-36%, such as 10%, 16%, 20% or 33%, where the percentage is the ratio of the mass of Rx in the second alloy to the mass of the second alloy.
[0047] In some embodiments, Rx includes Ho, Er, Tm or Y, and the ratio of the mass of Rx in the second alloy to the mass of R2 in the second alloy may be 30%-70%, preferably 45%-70%, such as 49.19%, 59.29%, 62.50% or 66.67%. The ratio of the mass of the second alloy to the sum of the masses of the first alloy and the second alloy may be 1%-5%, such as 2%, 3%, 4% or 5%.
[0048] In some embodiments, Rx is only Pr, R2 is only Rx, and the ratio of the mass of the second alloy to the sum of the mass of the first alloy and the second alloy may be ≤3%.
[0049] In the present invention, R2 may further include R2-1, and R2-1 includes one or more of Nd, Dy and Tb.
[0050] In the present invention, in step S1, the content of B element in the second alloy may be 0.8%-1.0%, such as 0.88%, 0.92%, 0.94% or 0.96%, where the percentage is the ratio of the mass of B element in the second alloy to the mass of the second alloy.
[0051] In the present invention, in step S1, the second alloy may further include an M element, where M is one or more of Cu, Al, Co, Ga, Zr and Ti.
[0052] Preferably, the second alloy also includes one or more of Al, Cu and Ga, wherein the total amount of Al, Cu and Ga in the second alloy may be <1.5%, for example, 0.35% or 1.25%, and the percentage is the ratio of the sum of the masses of Al, Cu and Ga elements in the second alloy to the mass of the second alloy.
[0053] In a specific embodiment of the present invention, the composition of the second alloy is: Nd 12%, Ho 16%, Pr 4%, Fe 66.77%, Cu 0.35% and B 0.88%, and the percentage is the ratio of the mass of each element in the second alloy to the mass of the second alloy.
[0054] In a specific embodiment of the present invention, the composition of the second alloy is: Nd 15.75%, Er 10%, Pr 5.25%, Fe 67.73%, Ga 0.35% and B 0.92%, and the percentage is the ratio of the mass of each element in the second alloy to the mass of the second alloy.
[0055] In a specific embodiment of the present invention, the composition of the second alloy is: Nd 12%, Tm 20%, Pr 4%, Fe 61.81%, Cu 1.05%, Ga 0.2% and B 0.94%, and the percentage is the ratio of the mass of each element in the second alloy to the mass of the second alloy.
[0056] In a specific embodiment of the present invention, the composition of the second alloy is: Nd 14.25%, Y 16%, Pr 4.75%, Fe 62.81%, Cu 1.05%, Ga 0.2% and B 0.94%, where the percentage is the ratio of the mass of each element in the second alloy to the mass of the second alloy. The Nd and Pr elements in the second alloy may come from a PrNd alloy.
[0057] In a specific embodiment of the present invention, the composition of the second alloy is: Pr 33%, Fe 65.69%, Cu 0.35% and B 0.96%, and the percentage is the ratio of the mass of each element in the second alloy to the mass of the second alloy.
[0058] In the present invention, in step S1, smelting, casting, powder making, pressing and sintering are all carried out by conventional methods in the art.
[0059] In the present invention, in step S1, the smelting is carried out by a conventional method in the art. For example, the smelting is carried out in a high-frequency vacuum induction melting furnace, and the vacuum degree of the smelting can be 5×10 -2 Pa, the smelting temperature may be below 1500°C, for example 1480°C.
[0060] In the present invention, in step S1, the casting is performed by conventional methods in the art, for example, cooling after smelting. The atmosphere during the cooling may be an inert gas atmosphere, such as argon. The pressure during the cooling may be 5.5×10 4 Pa. The cooling rate during cooling can be 10 2 -10 4 ℃ / s.
[0061] In the present invention, in step S1, the powder making is carried out by conventional methods in the art, which may include hydrogen crushing and airflow milling in sequence. The steps of hydrogen crushing may include: hydrogen absorption, dehydrogenation and cooling. During the hydrogen absorption, the purity of hydrogen may be 99.99% or more. During the hydrogen absorption, the pressure of hydrogen may be 0.15MPa. The dehydrogenation may be carried out by heating. The heating may be vacuumed. The atmosphere of the airflow mill may be nitrogen. The pressure of the airflow mill may be 0.38MPa. The content of oxidizing gas in the atmosphere of the airflow mill may be 100ppm or less. The oxidizing gas may be oxygen or water.
[0062] In the present invention, in step S1, the pressing is carried out by a conventional method in the art, which may include magnetic field orientation pressing and cold isostatic pressing in sequence. The cold isostatic pressing may further densify the green body. The magnetizing magnetic field of the magnetic field orientation pressing may be 1-1.5T, for example, 1.2T; the pressure of the magnetic field orientation pressing may be 8-20T, for example, 10T. The pressure of the cold isostatic pressing may be 150-300MPa, for example, 200MPa.
[0063] In the present invention, in step S1, the sintering can be performed by conventional methods in the art. The sintering temperature can be 900-1100° C., such as 1080° C.; the sintering time can be 2-8 hours, preferably 3-6 hours.
[0064] In the present invention, in step S2, the specific step of the grain boundary diffusion may include: coating a diffusion source containing Rh on the surface of the substrate, and heating. The surface of the substrate may be cleaned before the coating. Drying may be performed before the heating. The heating temperature may be 750-950° C., for example, 850° C. The heating time may be 12-48 hours, for example, 24 hours. Cooling may be performed after the heating.
[0065] In the present invention, in step S2, the Rh-containing diffusion source may include one or more of a single substance, an oxide, a fluoride, a hydride and an alloy of Rh.
[0066] In the present invention, in step S2, the amount of Rh introduced by diffusion may be less than 1.2%, such as 0.4%, 0.5%, 0.6% or 0.8%, where the percentage refers to the ratio of the mass of Rh introduced by grain boundary diffusion to the mass of the RTB rare earth permanent magnet material.
[0067] In the present invention, in step S3, the aging is performed by a conventional method in the art. The aging temperature may be 450-650° C., for example, 500° C. The aging time may be 3-12 hours, for example, 5 hours.
[0068] In a third aspect, the present invention further provides an RTB rare earth permanent magnet material prepared by the method for preparing the RTB rare earth permanent magnet material as described above.
[0069] In a fourth aspect, the present invention further provides an application of the above-mentioned RTB rare earth permanent magnet material in magnetic steel.
[0070] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0071] The reagents and raw materials used in the present invention are commercially available.
[0072] The positive and progressive effects of the present invention are:
[0073] (1) The RTB rare earth permanent magnet material of the present invention has R x and R h There is a specific distribution, and the magnet material achieves efficient and uniform diffusion of magnets with a thickness specification of 6-20mm.
[0074] (2) The RTB rare earth permanent magnet material of the present invention has excellent room temperature and high temperature magnetic properties; at 20°C, the remanence Br is above 13.9 kGs, and the intrinsic coercive force Hcj is above 27.10 kOe; at 150°C, the intrinsic coercive force Hcj is above 10.60 kOe, the squareness SQ is above 98.1%, and the Hd5 is above 10.33 kOe.
[0075] (3) When preparing the RTB rare earth permanent magnet material of the present invention, the content of the Rx multi-element alloy is controlled to form a special concentration distribution of the rare earth elements Rx and Rh; on the one hand, the concentration of Rx is low in the surface layer of the main phase grains, and Rh diffuses into it to form a shell layer with a high magnetocrystalline anisotropy field, thereby improving the magnet performance; on the other hand, the concentration of Rx in the epitaxial layer of the main phase grains is relatively high, which avoids excessive diffusion of Rh into the main phase of the grains and improves the utilization rate of heavy rare earths. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is a macroscopic Rh concentration distribution diagram of the RTB rare earth permanent magnet material in Example 5, from the surface to a depth of 600 μm;
[0077] Figure 2 This is the macroscopic Rh concentration distribution diagram of the RTB rare earth permanent magnet material in Comparative Example 1, from the surface to a depth of 600 μm;
[0078] Figure 3 The crystalline phase Rx concentration distribution diagram of the RTB rare earth permanent magnet material in Example 5 involves the grain boundary phase, the epitaxial layer of the main phase grain, the core of the main phase grain and the surface layer of the main phase grain;
[0079] Figure 4 This is a crystalline phase Rh concentration distribution diagram of the RTB rare earth permanent magnet material in Example 5, involving the grain boundary phase, the epitaxial layer of the main phase grain, the core of the main phase grain and the surface layer of the main phase grain. DETAILED DESCRIPTION
[0080] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0081] Examples 1-5 and Comparative Examples 1-4
[0082] A method for preparing an RTB rare earth permanent magnet material comprises the following steps:
[0083] (1) Ingredients: The ingredients are prepared according to the composition ratio of the main alloy A (i.e., the first alloy) and the sub-alloy B containing Rx (i.e., the second alloy) in Table 1-2. The addition ratio of the sub-alloy B is the ratio of the mass of the sub-alloy B to the sum of the mass of the main component alloy A and the sub-alloy B.
[0084] (2) Melting: The metal material is melted by induction melting in a high-frequency vacuum induction melting furnace. Before melting, the furnace body is evacuated to a vacuum degree of 5×10 -2 Pa, the smelting temperature is 1480℃, so that the metal materials are melted into a uniformly mixed molten alloy liquid.
[0085] (3) Casting: After smelting, argon gas is introduced into the smelting furnace to a pressure of 5.5×10 4 After Pa, 10 4 The rapidly cooled alloy was obtained at a cooling rate of ℃ / s.
[0086] (4) Hydrogen pulverization process: The hydrogen pulverization furnace containing the rapidly cooled alloy is evacuated at room temperature, and then hydrogen with a purity of 99.99% is introduced into the hydrogen pulverization furnace, and the hydrogen pressure is maintained at 0.15 MPa. After sufficient hydrogen absorption, the temperature is increased while evacuating the furnace to fully dehydrogenate, and then the furnace is cooled and the coarse powder after hydrogen pulverization is taken out.
[0087] (5) Airflow milling: In a nitrogen atmosphere with an oxidizing gas content of less than 100 ppm and a crushing chamber pressure of 0.38 MPa, the coarse powder after hydrogen crushing is subjected to airflow milling to obtain a fine powder. The oxidizing gas refers to oxygen or water.
[0088] (6) Pressing: The fine powder is placed in a magnetic field press for magnetic field orientation pressing. The magnetizing magnetic field of the magnetic field orientation pressing is 1.2 T and the pressure of the magnetic field orientation pressing is 10 T. Then, the green body obtained by the magnetic field orientation pressing is subjected to 200 MPa cold isostatic pressing to obtain a green body.
[0089] (7) Sintering: The green body is sintered at a sintering temperature of 1080°C for 3 h. Then, argon gas is introduced to a pressure of 0.1 MPa and then cooled to room temperature to obtain the substrate.
[0090] (8) Diffusion: The substrate was processed into a magnet with a diameter of 20 mm and a thickness of 8 mm, with the thickness direction being the magnetic field orientation direction. After the surface was cleaned, a diffusion source prepared from Rh powder was used. The amount of Rh introduced was shown in Table 2. The diffusion source was coated on the surface of the substrate. The coated substrate was dried and diffused at 850°C for 24 h.
[0091] (9) Aging: The diffusion treated substrate is kept at 500°C for 3 hours and then cooled to obtain the RTB rare earth permanent magnet material.
[0092] Table 1 Element composition of main alloy A and sub-alloy B (wt%)
[0093] Nd Dy Ho Er Tm Y Pr Fe Co Cu Ga B Ti Main Alloy A 22.28 0.5 0 0 0 0 7.43 67.25 1 0.2 0.2 0.95 0.2 Sub-alloy B-1 12 0 16 0 0 0 4 66.77 0 0.35 0 0.88 0 Sub-alloy B-2 15.75 0 0 10 0 0 5.25 67.73 0 0 0.35 0.92 0 Sub-alloy B-3 12 0 0 0 20 0 4 61.81 0 1.05 0.2 0.94 0 Sub-alloy B-4 14.25 0 0 0 0 16 4.75 62.81 0 1.05 0.2 0.94 0 Sub-alloy B-5 0 0 0 0 0 0 33 65.69 0 0.35 0 0.96 0 Sub-alloy B-6 18.75 0 0 6 0 0 6.25 67.73 0 0.25 0.1 0.92 0 Sub-alloy B-7 12 0 0 0 13 0 4 69.66 0 0.2 0.2 0.94 0 Sub-alloy B-8 14.25 0 0 0 0 16 4.75 63.56 0 0.2 0.3 0.94 0
[0094] Table 2 Element ratios in Examples 1-5 and Comparative Examples 1-4
[0095]
[0096] Effect Example 1: Analysis of rare earth element concentration distribution
[0097] 1. Test object: RTB rare earth permanent magnet material in Example 5 and Comparative Example 1.
[0098] 2. Test method: After the RTB rare earth permanent magnet material is cross-sectioned and polished, it is analyzed using a field emission electron probe microanalyzer (EPMA, JEOL Ltd., model 8530F). First, the element distribution is scanned at a depth of 0-600μm to obtain the macro element concentration distribution, and then the surface of the RTB rare earth permanent magnet material is scanned at a high magnification to obtain the element concentration distribution at different positions.
[0099] 3. Test results:
[0100] The test results of the macro element concentration distribution of the RTB rare earth permanent magnet material in Example 5 are as follows: Figure 1 As shown, the upper part represents the surface distribution of heavy rare earth Tb. Different colors represent different signal intensities of characteristic X-rays collected by the equipment. The higher the signal intensity, the lighter the color, and the higher the corresponding element content, as shown on the right ruler. The lower part converts the surface distribution results into numerical values. The horizontal axis represents the depth from the sample surface to 600μm, and the vertical axis represents the Tb content. The value is converted by the equipment according to its own standard sample database to convert the signal intensity. Relative comparison can be performed within the same visual field test area. From the results, it can be seen that the overall Tb distribution in the RTB rare earth permanent magnet material of Example 5 is uniform, without obvious gradient changes, that is, |C0-C 200 |≤1%,|C 200 -C 400 |≤1%,|C 400 -C 600 |≤1%,C 0-200 It refers to the integrated average value of the concentration of Rh in the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 200 μm from the surface, C 200-400It refers to the integral average value of the concentration of Rh in the interval from 200 μm to 400 μm vertically away from the surface in the RTB rare earth permanent magnet material, C 400-600 It refers to the integrated average value of the Rh concentration in the interval from 400 μm to 600 μm vertically away from the surface in the RTB rare earth permanent magnet material.
[0101] The test results of the macro element concentration distribution of the RTB rare earth permanent magnet material in Comparative Example 1 are as follows: Figure 2 As shown, it can be seen that the concentration of heavy rare earth Tb gradually decreases from the surface to the center of the sample. As the depth increases, the diffusion effect weakens and the overall consistency is poor.
[0102] The surface of the RTB rare earth permanent magnet material in Example 5 was further scanned at a high magnification using an EPMA device. The results are as follows: Figure 3 and Figure 4 As shown, Figure 3 The distribution of Rx element Pr, the concentration distribution of Rx satisfies: grain boundary phase>main phase grain epitaxial layer>main phase grain core≥main phase grain surface layer; Figure 4 is the distribution of Rh element Tb, and the concentration distribution of Rh satisfies: surface layer of main phase grain > grain boundary phase ≥ epitaxial layer of main phase grain > core of main phase grain, as shown in Table 3.
[0103] In comparative example 1, the addition ratio of sub-alloy B-1 is too high, resulting in a final Rx content that is too high, a high Rx concentration in the surface layer of the main phase grains, and less surface dissolution during diffusion, so the Rh content in the surface layer of the main phase and the epitaxial layer is close, and the concentration in the grain boundary phase is too high. In comparative example 2, sub-alloy B-6 with a lower Rx content is used, so that the addition amount of Rx is too low, that is, the Rx / R concentration ratio is too low, resulting in a Rh concentration close to the surface layer of the main phase grains and the epitaxial layer of the main phase grains, and the Rx concentration is also close. In comparative example 3, sub-alloy B-7 with a lower rare earth element R content is used, resulting in a Rh concentration close to the surface layer of the main phase grains and the epitaxial layer of the main phase grains, and the Rx concentration is also close. In comparative example 4, the addition ratio of sub-alloy B-8 is too low, and the final Rx content is too low, resulting in a Rh concentration close to the surface layer of the main phase grains and the epitaxial layer of the main phase grains, and the Rx concentration is also close, and the Rh concentration in the core of the main phase grains is too high.
[0104] Table 3 Rare earth element concentration distribution on the surface of R-TB rare earth permanent magnet material (unit: %)
[0105]
[0106] Effect Example 2: Magnetic Performance Parameters Test
[0107] 1. Test object: RTB rare earth permanent magnet materials in Examples 1-5 and Comparative Examples 1-4.
[0108] 2. Test method: The magnetic properties of RTB rare earth permanent magnet materials were tested using the NIM-62000 permanent magnet material precision measurement system of the China Institute of Metrology. The test temperatures were 20°C and 150°C.
[0109] 3. Test results: The results of the remanence test, coercivity test, squareness test and Hd5 test are shown in Table 4.
[0110] Table 4
[0111]
[0112] In Examples 1-5, since the concentration distribution of Rx satisfies: grain boundary phase>main phase grain epitaxial layer>main phase grain core≥main phase grain surface, and the concentration distribution of Rh satisfies:main phase grain surface>grain boundary phase≥main phase grain epitaxial layer>main phase grain core, the magnetic properties of RTB rare earth permanent magnet material at 20°C and 150°C are good.
[0113] In Comparative Examples 1-4, since the Rh concentrations in the surface layer of the main phase grains and the epitaxial layer of the main phase grains are close, the Rx concentrations are also close, which does not meet the Rx and Rh concentration distribution of the present invention, resulting in serious deterioration of the magnetic properties at 150°C.
Claims
1. An RTB rare earth permanent magnet material, characterized in that: It comprises main phase grains and grain boundary phases, wherein the main phase grains include, from outside to inside, a main phase grain surface layer, a main phase grain epitaxial layer and a main phase grain core; The RTB rare earth permanent magnet material includes Rx and Rh, Rx includes one or more of Pr, Ho, Er, Tm, Y and Lu, and Rh includes Dy and / or Tb; The concentration distribution of Rx satisfies: grain boundary phase>main phase grain epitaxial layer>main phase grain core≥main phase grain surface layer, and the concentration of Rx refers to the ratio of the mass of Rx at that location to the mass of the RTB rare earth permanent magnet material; The concentration distribution of Rh satisfies: surface layer of main phase grain>grain boundary phase≥epitaxial layer of main phase grain>core of main phase grain, and the concentration of Rh refers to the ratio of the mass of Rh at that location to the mass of the RTB rare earth permanent magnet material.
2. The RTB rare earth permanent magnet material according to claim 1, characterized in that: The ratio of the concentration of Rx in the core of the main phase grain to the concentration of Rx in the surface layer of the main phase grain is (1.0-2.5):1, for example, 1.8:1.1, 1.9:0.8, 2.2:1.3, 1.7:0.7 or 2.1:1.2; and / or, the ratio of the concentration of Rx in the surface layer of the main phase grains to the concentration of Rx in the epitaxial layer of the main phase grains is 1:(3.0-6.0), for example, 1.1:3.8, 0.8:3.7, 1.3:4.2, 0.7:3.6 or 1.2:4.1; and / or, the ratio of the concentration of Rx in the main phase grain epitaxial layer to the concentration of Rx in the grain boundary phase is 1:(2.0-3.0), for example, 3.8:8.7, 3.7:8.6, 4.2:9.1, 3.6:9.5 or 4.1:8.9; and / or, the ratio of the concentration of Rh in the core of the main phase grains to the concentration of Rh in the surface layer of the main phase grains is 1:(15.0-20.0), for example, 0.48:7.8, 0.45:8.5, 0.51:8.6, 0.53:9.0 or 0.50:8.2; and / or, the ratio of the concentration of Rh in the surface layer of the main phase grains to the concentration of Rh in the epitaxial layer of the main phase grains is (2.0-2.5):1, for example, 7.8:3.6, 8.5:3.7, 8.6:3.5, 9.0:4.5 or 8.2:3.9; and / or, the ratio of the Rh concentration of the main phase grain epitaxial layer to the Rh concentration of the grain boundary phase is 1:(1.0-1.2), for example, 3.6:3.8, 3.7:3.9, 3.5:4.1, 4.5:5.2 or 3.9:4.0; And / or, within the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of at least 600 μm from the surface, the concentration distribution of Rh satisfies: surface layer of main phase grains>grain boundary phase≥epitaxial layer of main phase grains>core of main phase grains; preferably, within the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 800 μm from the surface, the concentration distribution of Rh may satisfy: surface layer of main phase grains>grain boundary phase≥epitaxial layer of main phase grains>core of main phase grains; And / or, within the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of at least 600 μm from the surface, the concentration distribution of Rx satisfies: grain boundary phase>main phase crystal grain epitaxial layer>main phase crystal grain core≥main phase crystal grain surface layer; preferably, within the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 800 μm from the surface, the concentration distribution of Rx may satisfy: grain boundary phase>main phase crystal grain epitaxial layer>main phase crystal grain core≥main phase crystal grain surface layer; And / or, the Rh concentration distribution also satisfies: |C 0-200 -C 200-400 |≤1%,|C 200-400 -C 400-600 |≤1%,C 0-200 It refers to the integrated average value of the concentration of Rh in the interval from the surface of the RTB rare earth permanent magnet material to a vertical distance of 200 μm from the surface, C 200-400 It refers to the integral average value of the concentration of Rh in the interval from 200 μm to 400 μm vertically away from the surface in the RTB rare earth permanent magnet material, C 400-600 It refers to the integrated average value of the Rh concentration in the interval from 400 μm to 600 μm vertically away from the surface in the RTB rare earth permanent magnet material.
3. The RTB rare earth permanent magnet material according to claim 1, characterized in that: The RTB rare earth permanent magnet material further includes an M element, where M is one or more of Cu, Al, Co, Ga, Zr and Ti; And / or, the Rx and the Rh are introduced in the following manners: ① or ②: ① The Rx is introduced in the form of a multi-element alloy component, and the Rh is introduced by grain boundary diffusion; ② The Rx is introduced in the form of a multi-element alloy component, and part of the Rh is introduced through grain boundary diffusion and part is introduced in the form of a multi-element alloy component.
4. A method for preparing RTB rare earth permanent magnet material, characterized in that: It includes the following steps: S1, smelting, casting, powdering, pressing and sintering the first alloy and the second alloy to obtain a substrate; The first alloy includes R1, Fe and B elements, and the second alloy includes R2, Fe and B elements; R1 includes one or more of Nd, Dy and Tb, R2 includes Rx, and Rx includes one or more of Pr, Ho, Er, Tm, Y and Lu; In the substrate, the content of Rx is 0.2%-1%, and the percentage is the ratio of the mass of Rx to the mass of the substrate; S2, performing grain boundary diffusion on the substrate using a diffusion source containing Rh, wherein Rh includes Dy and / or Tb; S3, subjecting the diffusion treated substrate to aging treatment.
5. The method for preparing the RTB rare earth permanent magnet material according to claim 4, characterized in that: In step S1, the content of R1 in the first alloy is 29%-36%, for example, 30.21%, where the percentage is the ratio of the mass of R1 in the first alloy to the mass of the first alloy; And / or, in step S1, the content of the B element in the first alloy is 0.8%-1.0%, for example, 0.95%, where the percentage is the ratio of the mass of the B element in the first alloy to the mass of the first alloy; And / or, in step S1, the first alloy further includes an M element, where M is one or more of Cu, Al, Co, Ga, Zr and Ti; Preferably, the first alloy further comprises one or more of Al, Cu and Ga, wherein the total amount of Al, Cu and Ga in the first alloy is preferably less than 1.5%, for example, 0.4%, and the percentage is the ratio of the sum of the mass of the Al, Cu and Ga elements in the first alloy to the mass of the first alloy; More preferably, the composition of the first alloy is: Nd 22.28%, Dy 0.5%, Pr 7.43%, Fe67.25%, Co1%, Cu 0.2%, Ga 0.2%, B 0.95% and Ti 0.2%, where the percentage is the ratio of the mass of each element in the first alloy to the mass of the first alloy; the Nd and Pr elements in the first alloy preferably come from a PrNd alloy.
6. The method for preparing the RTB rare earth permanent magnet material according to claim 4, characterized in that: In step S1, the content of R2 in the second alloy is 29%-36%, such as 31%, 32%, 33%, 35% or 36%, where the percentage is the ratio of the mass of R2 in the second alloy to the mass of the second alloy; and / or, in step S1, the content of Rx in the second alloy is 10%-36%, for example, 10%, 16%, 20% or 33%, where the percentage is the ratio of the mass of Rx in the second alloy to the mass of the second alloy; And / or, Rx includes Ho, Er, Tm or Y, the ratio of the mass of Rx in the second alloy to the mass of R2 in the second alloy is 30%-70%, preferably 45%-70%, such as 49.19%, 59.29%, 62.50% or 66.67%; the ratio of the mass of the second alloy to the sum of the masses of the first alloy and the second alloy is preferably 1%-5%, such as 2%, 3%, 4% or 5%; and / or, Rx is Pr, R2 is Rx; the ratio of the mass of the second alloy to the sum of the mass of the first alloy and the second alloy is preferably ≤3%; And / or, R2 further includes R2-1, and R2-1 includes one or more of Nd, Dy and Tb; And / or, in step S1, the content of B element in the second alloy is 0.8%-1.0%, such as 0.88%, 0.92%, 0.94% or 0.96%, where the percentage is the ratio of the mass of B element in the second alloy to the mass of the second alloy; And / or, in step S1, the second alloy further includes an M element, and M includes one or more of Cu, Al, Co, Ga, Zr and Ti; Preferably, the second alloy further comprises one or more of Al, Cu and Ga, wherein the total amount of Al, Cu and Ga in the second alloy is preferably less than 1.5%, for example, 0.35% or 1.25%, and the percentage is the ratio of the sum of the mass of the Al, Cu and Ga elements in the second alloy to the mass of the second alloy; More preferably, the composition of the second alloy is any one of the following compositions ①-⑤, and the percentage is the ratio of the mass of each element in the second alloy to the mass of the second alloy: ①Nd 12%, Ho 16%, Pr 4%, Fe 66.77%, Cu 0.35% and B 0.88%; ②Nd 15.75%, Er 10%, Pr 5.25%, Fe 67.73%, Ga 0.35% and B 0.92%; ③Nd 12%, Tm 20%, Pr 4%, Fe 61.81%, Cu 1.05%, Ga 0.2% and B 0.94%; ④ Nd 14.25%, Y 16%, Pr 4.75%, Fe 62.81%, Cu 1.05%, Ga 0.2% and B 0.94%, Nd and Pr elements preferably come from PrNd alloy; ⑤Pr 33%, Fe 65.69%, Cu 0.35% and B 0.96%.
7. The method for preparing the RTB rare earth permanent magnet material according to claim 4, characterized in that: In step S1, the total amount of all rare earth elements R in the substrate is 29%-36%, preferably 30.2%-30.4%, where the percentage is the ratio of the mass of all rare earth elements R to the mass of the substrate; And / or, in step S1, the substrate further comprises an M element, M comprises one or more of Cu, Al, Co, Ga, Zr and Ti; the M element is preferably derived from the first alloy and / or the second alloy; and / or, in step S1, the content of Rx in the substrate is 0.3%-1%, for example, 0.32%, 0.40%, 0.60%, 0.80% or 0.99%; And / or, in step S1, the smelting is induction smelting, preferably, carried out in a high frequency vacuum induction smelting furnace, and the vacuum degree of the smelting is 5×10 -2 Pa, the smelting temperature is below 1500°C, for example 1480°C; And / or, in step S1, the casting step includes: cooling the molten alloy liquid obtained after smelting; the atmosphere during the cooling is preferably an inert gas atmosphere, such as argon; the pressure during the cooling is, for example, 5.5×10 4 Pa; the cooling rate during the cooling is, for example, 10 2 -10 4 °C / s; And / or, in step S1, the pulverizing comprises hydrogen crushing and airflow milling in sequence; the hydrogen crushing and pulverizing steps preferably comprise: hydrogen absorption, dehydrogenation and cooling; during the hydrogen absorption, the purity of hydrogen is preferably 99.99% or above; during the hydrogen absorption, the pressure of hydrogen is preferably 0.15MPa; the dehydrogenation is preferably performed by heating; the heating is preferably performed by vacuuming; the atmosphere of the airflow mill is preferably nitrogen; the pressure of the airflow mill is preferably 0.38MPa; the content of oxidizing gas in the atmosphere of the airflow mill is preferably 100ppm or below; the oxidizing gas is preferably oxygen or water; And / or, in step S1, the pressing steps include magnetic field orientation pressing and cold isostatic pressing in sequence; the magnetizing magnetic field of the magnetic field orientation pressing is preferably 1-1.5T, such as 1.2T; the pressure of the magnetic field orientation pressing is preferably 8-20T, such as 10T; the pressure of the cold isostatic pressing is preferably 150-300MPa, such as 200MPa; And / or, in step S1, the sintering temperature is 900-1100°C, for example, 1080°C; And / or, in step S1, the sintering time is 2-8 hours, preferably 3-6 hours.
8. The method for preparing the RTB rare earth permanent magnet material according to claim 4, characterized in that: In step S2, the amount of Rh introduced by diffusion is less than 1.2%, such as 0.4%, 0.5%, 0.6% or 0.8%, where the percentage refers to the ratio of the mass of Rh introduced by grain boundary diffusion to the mass of the RTB rare earth permanent magnet material; And / or, in step S2, the specific steps of the grain boundary diffusion include: coating the surface of the substrate with a diffusion source containing Rh, and heating; preferably cleaning the surface of the substrate before coating; preferably drying before heating; preferably the heating temperature is 750-950° C., for example, 850° C.; preferably the heating time is 12-48 hours, for example, 24 hours; preferably cooling after heating; and / or, in step S2, the Rh-containing diffusion source comprises one or more of a single substance, an oxide, a fluoride, a hydride and an alloy of Rh; And / or, in step S3, the aging temperature is 450-650°C, for example, 500°C; And / or, in step S3, the aging time is 3-12 hours, for example, 5 hours.
9. An RTB rare earth permanent magnet material obtained by the method for preparing an RTB rare earth permanent magnet material according to any one of claims 4 to 8.
10. Use of the RTB rare earth permanent magnet material according to any one of claims 1 to 3 and 9 in magnetic steel.
Citation Information
Patent Citations
Neodymium-iron-boron magnet material and preparation method thereof
CN115020057A